Essential Tremor and Dementia: Incidental Co-Occurrence or Real Association in Aging? - Eker, Amber (Asia Pacific League Clinical Gerontology & Geriatrics, 2024)
Essential tremor (ET) was considered to be mono-symptomatic. However, it has been reported recently that motor and non-motor findings other than kinetic tremor may accompany the disease. The records of the cases evaluated in the dementia policlinics were retrospectively analyzed. The demographic and clinical characteristics of cases with dementia and isolated kinetic tremors were noted. There were 8 patients diagnosed with dementia in the follow-up after the presentation with ET. The mean onset age of the kinetic tremor was 65.75 years. Parkinsonian findings were observed in the follow-up of 6 patients. The neurocognitive evaluation revealed depression, dysfunction in attention, and visuospatial skills in half of the patients. The clinical picture is compatible with dementia with Lewy bodies in half of our ET cases with dementia. ET is now recognized as a neurodegenerative disease accompanied by neurological symptoms other than kinetic tremor. This report supported that other neurodegenerative diseases may accompany ET.
Keywords: Essential tremor; dementia; parkinsonism; Essential tremor; dementia; parkinsonism; dementia with Lewy bodies